PENGARUH KUALITAS PELAYANAN KERETA COMMUTER INDONESIA TERHADAP KEPUASAN WISATAWAN DOMESTIK PADA ERA KENORMALAN BARU - Nosita Elika; I Made Sendra; Ni Putu Eka Mahadewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2021)
The Indonesian Commuter Train is a favorite mass transportation for traveling in greater Jakarta because of its affordable price, proximity of the station to tourist destinations, and the services provided. In fact, the management has prepared special Passenger Service officers. There was a decline in passengers in 2019 due to passenger dissatisfaction with the services provided, even the ratio of the number of passenger complaints in 2019-2020 was still the same. In fact, as a commitment to the continued operation during the pandemic, the management launched a special Passenger Service officer named C-Ranger to disseminate health protocols during the new normal. This study uses mixed methods data analysis techniques including qualitative and quantitative descriptive analysis. The research sample determination technique uses purposive sampling with a sample size of 100 respondents. The results of the study show services provided by Passenger Service are ticketing, information service, complaint handling, CCTV access information, priority passenger, pregnant wowen, Lost and Found, and C-Ranger. Based on the t test showed that partially, the variables with tangible, assurance, and reliability variables had a significant influence on the satisfaction of domestic tourists. While the variables of empathy and responsiveness do not have a significant effect on the satisfaction of domestic tourists. simultaneously the quality of Passenger Service has a significant and positive influence on the satisfaction of domestic tourists with a coefficient of determination of 50.7%.